Whole mitogenome sequencing uncovers a relation between mitochondrial heteroplasmy and leprosy severity - Felipe Gouvea de Souza; Moisés Batista da Silva; Gilderlanio S. de Araújo; Caio S. Silva; Andrey Henrique Gama Pinheiro; Miguel Ángel Cáceres-Durán; Mayara Natália Santana-da-Silva; Pablo Pinto; Angélica Rita Gobbo; Patrícia Fagundes da Costa; Claudio Guedes Salgado; Ândrea Ribeiro-dos-Santos; et al. (Human Genomics, 2023)
Abstract Background In recent years, the mitochondria/immune system interaction has been proposed, so that variants of mitochondrial genome and levels of heteroplasmy might deregulate important metabolic processes in fighting infections, such as leprosy. Methods We sequenced the whole mitochondrial genome to investigate variants and heteroplasmy levels, considering patients with different clinical forms of leprosy and household contacts. After sequencing, a specific pipeline was used for preparation and bioinformatics analysis to select heteroplasmic variants. Results We found 116 variants in at least two of the subtypes of the case group (Borderline Tuberculoid, Borderline Lepromatous, Lepromatous), suggesting a possible clinical significance to these variants. Notably, 15 variants were exclusively found in these three clinical forms, of which five variants stand out for being missense (m.3791T > C in MT-ND1, m.5317C > A in MT-ND2, m.8545G > A in MT-ATP8, m.9044T > C in MT-ATP6 and m.15837T > C in MT-CYB). In addition, we found 26 variants shared only by leprosy poles, of which two are characterized as missense (m.4248T > C in MT-ND1 and m.8027G > A in MT-CO2). Conclusion We found a significant number of variants and heteroplasmy levels in the leprosy patients from our cohort, as well as six genes that may influence leprosy susceptibility, suggesting for the first time that the mitogenome might be involved with the leprosy process, distinction of clinical forms and severity. Thus, future studies are needed to help understand the genetic consequences of these variants.